Sepsis: evolving concepts and challenges - Salomão,R. (2019)
Sepsis remains a major cause of morbidity and mortality worldwide, with increased burden in low- and middle-resource settings. The role of the inflammatory response in the pathogenesis of the syndrome has supported the modern concept of sepsis. Nevertheless, a definition of sepsis and the criteria for its recognition is a continuous process, which reflects the growing knowledge of its mechanisms and the success and failure of diagnostic and therapeutic interventions. Here we review the evolving concepts of sepsis, from the “systemic inflammatory response syndrome triggered by infection” (Sepsis-1) to “a severe, potentially fatal, organic dysfunction caused by an inadequate or dysregulated host response to infection” (Sepsis-3). We focused in the pathophysiology behind the concept and the criteria for recognition and diagnosis of sepsis. A major challenge in evaluating the host response in sepsis is to characterize what is protective and what is harmful, and we discuss that, at least in part, the apparent dysregulated host response may be an effort to adapt to a hostile environment. The new criteria for recognition and diagnosis of sepsis were derived from robust databases, restricted, however, to developed countries. Since then, the criteria have been supported in different clinical settings and in different economic and epidemiological contexts, but still raise discussion regarding their use for the identification versus the prognostication of the septic patient. Clinicians should not be restricted to definition criteria when evaluating patients with infection and should wisely use the broad array of information obtained by rigorous clinical observation.